1988
DOI: 10.1080/08927018809378103
|View full text |Cite
|
Sign up to set email alerts
|

Biofouling in oilfield water systems—a review

Abstract: The literature on biofouling in oilfield water systems is reviewed and the implications of such fouling considered. The currently available methods for the detection and control of the causative organisms are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 34 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Although biofilms can play important and useful roles in many settings, much o f the effort to manage biofilms has focused on removing or controlling unwanted biofilm. Biofilms foul, corrode, and degrade many industrial products (Costerton, et al 1987;Notermans 1994;Lynch, et al 1988). The negative impact o f biofilms extends beyond measurement in dollars, as many diseases and infections are now recognized as being mediated by biofilms (Hoyle, et al 1991).…”
Section: List Of Tablesmentioning
confidence: 99%
“…Although biofilms can play important and useful roles in many settings, much o f the effort to manage biofilms has focused on removing or controlling unwanted biofilm. Biofilms foul, corrode, and degrade many industrial products (Costerton, et al 1987;Notermans 1994;Lynch, et al 1988). The negative impact o f biofilms extends beyond measurement in dollars, as many diseases and infections are now recognized as being mediated by biofilms (Hoyle, et al 1991).…”
Section: List Of Tablesmentioning
confidence: 99%
“…Due to the economic losses as well as environmental health and safety hazards caused by the activity of SRB, many industrial sectors such as the oil and gas industry (Pankhurst, 1968;Hamilton, 1983;Cord-Ruwisch et al, 1987;Lynch & Edyvean, 1988), the shipping industry (Hill, 1983) and civil engineering (Hamilton, 1985;Odum, 1990;Edyvean, 1990;Ghassem & Adibi, 1995) are seeking solutions to minimise the risks resulting from SRB activity. Chemical control by the use of biocides is probably the most common method of controlling biocorrosion (Brunt, 1987;Boivin, 1995).…”
Section: Introductionmentioning
confidence: 98%
“…Varying degrees of colonisation and microbial succession have been observed on different substrata, and detailed laboratory studies have revealed that rate of adhesion is dependent upon complex interactions between the substratum hydrophobicity, the bacterial hydrophobicity, and the surface tension of the aqueous phase (Absolom et al, 1983;Fletcher & Pringle, 1985;Gerson & Scheer, 1980). A brief review of current methods used to control biofilms is presented by Lynch and Edyvean (1988). A recently described approach to the prevention of bacterial adhesion (Owens et al, 1987) is based on treating hydrophobic substratum surfaces with a tri-block copolymer of polyethylene oxide and polypropylene oxide ('Synperonic' F108).…”
Section: Introductionmentioning
confidence: 98%